A case study of comparison on performance and operating cost between manual sickle and motorized cutter for harvesting operation in oil palm plantation / Gunawan Rosmen - Rosmen, Gunawan (Faculty of Plantation and Agrotechnology, 2016)
From this paper, it is an effort to investigate the most efficient harvesting tools that must be applied by all oil palm producer. It is similarly to identify which harvesting tools is the most efficient that reflected to the labor productivity and cost management for harvesting operation. The Motorized cutter and manual sickle was tested based on capacity and cost involve. Trials carried out on motorized cutter revealed that the productivity of the machine was around 450 bunches per day (7.4 tonne per day at average bunch weight l7kg). The productivity depends on the cropping level, field condition, and the operator skill. Comparing to the manual sickle, is only around 250 bunches per day (4.2 tonne per day). Therefore, by using motorized cutter the estate would reduce 50% of its labour requirement in the harvesting operation. In addition the EFC for motorized is superior than manual with 0.29 ha per hour for motorized and 0.22 ha per hour for manual. As for the cost involved in both harvesting tools, the motorized curter cost is RM 4500 plus its operational costs, the harvesting cost comes to RM 8.78 per tonne and for the manual sickle cost is RM 143 plus its operating cost, it comes to RM 10.14 per tonne.